Economic shocks, tax revenues and budget dynamics: macroeconomic impact on business statistics in Ukraine (2010–2022) - Robert Bacho; Бачо Роберт; Bacsó Róbert; Gabriella Loskorikh; Лоскоріх Габріелла; Loszkorih Gabriella; Gabor Pataki; Потокі Габор; Pataki Gábor; Oksana Perchi; Перчі Оксана; Pércsi Oxána (ТОВ «ДКС Центр», 2025)
Abstract. The article examines the impact of economic shocks on entrepreneurial activity in Ukraine from 2010 to 2022,particularly focusing on the global financial and economic crisis, the annexation of Crimea, the COVID-19 pandemic,and the Russo-Ukrainian War. In the context of globalization and the integration of national economies into the globaleconomic system, as well as under the influence of unexpected internal and external changes, the national economyundergoes significant transformations, which have a particular impact on countries with transitional economies such asUkraine. External economic shocks and internal factors create conditions for unstable development in the entrepreneurialenvironment, presenting important tasks for both the government and businesses to adapt to rapidly changing conditions. The article specifically focuses on analyzing changes in the structure and number of enterprises of various types: micro-, small, medium, and large. It explores the relationship between macroeconomic factors and business activity, and alsoanalyzes changes in tax revenues and the country's budget dynamics in the context of crises. A comparison of Ukraine'seconomic indicators with corresponding data from the European Union helps to identify synchronous and asynchronoustrends in the development of both economies. Comparative and statistical analysis methods have been applied to studychanges in the number of enterprises, as well as correlation and regression analysis to assess the relationship betweenmacroeconomic factors and business activity. The scientific methods used provide a comprehensive picture of changesin Ukraine's business environment under the influence of economic shocks and contribute to a deeper understanding ofentrepreneurial activity dynamics in crisis situations. The study results indicate a significant impact of economic criseson entrepreneurial activity in Ukraine, particularly on small businesses, which have proven to be the most vulnerable toeconomic upheavals. Timely adaptation to economic changes, effective management of state resources, the developmentof the tax system, and support for small and medium-sized enterprises are key aspects for ensuring the sustainability ofeconomic growth and social stability in the face of both external and internal challenges.

Резюме. Стаття досліджує вплив економічних шоків на підприємницьку активність в Україні в період 2010—2022 років,зокрема глобальної фінансово-економічної кризи, анексії Криму, пандемії COVID-19 та російсько-української війни.В умовах глобалізації та інтеграції національних економік у світову економічну систему, а також під впливом нео-чікуваних внутрішніх і зовнішніх змін, національна економіка зазнає значних трансформацій, що мають особливийвплив на країни з перехідною економікою, такі як Україна. Зовнішні економічні шоки та внутрішні фактори створю-ють умови для нестабільного розвитку підприємницького середовища, що ставить перед урядом і бізнесом важливізавдання адаптації до швидко змінюваних умов. У статті окрему увагу приділено аналізу змін у структурі та кількостіпідприємств різних типів: мікро-, малих, середніх і великих. Досліджено взаємозв'язок між макроекономічними фак-торами і діяльністю бізнесу, а також проаналізовано зміни в податкових надходженнях та бюджетній динаміці країни в умовах криз. Порівняння економічних показників України з аналогічними даними ЄС дозволяє виявити синх-ронні та асинхронні тенденції в розвитку обох економік. Застосовано методи порівняльного та статистичного аналізу для вивчення змін у кількості підприємств, а також кореляційно-регресійний аналіз для оцінки взаємозв'язку міжмакроекономічними чинниками та активністю бізнесу. Використані наукові методи дозволяють отримати комплексну картину змін у бізнес-середовищі України під впливом економічних шоків і сприяють глибшому розумінню динаміки підприємницької активності в умовах кризових ситуацій. Результати дослідження вказують на суттєвий впливекономічних криз на підприємницьку активність в Україні, зокрема на малий бізнес, який виявився найбільш вразли-вим до економічних потрясінь. Своєчасна адаптація до економічних змін, ефективне управління державними ресур-сами, розвиток податкової системи та підтримка малого та середнього бізнесу є важливими аспектами для забезпечення стійкості економічного зростання та соціальної стабільності в умовах зовнішніх і внутрішніх викликів.
Економічні шоки, податкові надходження та бюджетна динаміка: макроекономічний вплив на бізнес-статистику в Україні (2010–2022 роки)
Весь випуск: https://nayka.com.ua/index.php/agrosvit/issue/view/235
Keywords: economic shocks; tax revenues; taxes; budget dynamics; budget